2020
DOI: 10.3390/nano10071333
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Defects for Ratiometric Luminescence Thermometry

Abstract: In luminescence thermometry enabling temperature reading at a distance, an important challenge is to propose new solutions that open measuring and material possibilities. Responding to these needs, in the nanocrystalline phosphors of yttrium oxide Y2O3 and lutetium oxide Lu2O3, temperature-dependent emission of trivalent terbium Tb3+ dopant ions was recorded at the excitation wavelength 266 nm. The signal of intensity decreasing with temperature was monitored in the range corresponding to the 5D4 → 7F6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…[ 44 ] In another study on Tb 3+ ‐doped Ln 2 O 3 (Ln = Y, Lu) sesquioxides, Drabik et al . [ 45 ] observed that, for a 10‐fold increase in Tb 3+ concentration, shortening of average lifetimes reached only 4–7% of the initial value obtained for the lowest dopant concentration. Shortening of lifetime is usually observed as Tb 3+ concentration increases.…”
Section: Resultsmentioning
confidence: 99%
“…[ 44 ] In another study on Tb 3+ ‐doped Ln 2 O 3 (Ln = Y, Lu) sesquioxides, Drabik et al . [ 45 ] observed that, for a 10‐fold increase in Tb 3+ concentration, shortening of average lifetimes reached only 4–7% of the initial value obtained for the lowest dopant concentration. Shortening of lifetime is usually observed as Tb 3+ concentration increases.…”
Section: Resultsmentioning
confidence: 99%
“…18,43 The discrepancy of the thermally responsive emission intensity variation between Eu 2+ and Eu 3+ qualifies the BMPO: Eu phosphors with potential application for ratiometric optical thermometry. 44 The FIR of Eu 2+ at 410 nm on Eu 3+ at 596, 619, and 699 nm was calculated, respectively, as the temperature measurement index. As depicted in Fig.…”
Section: Thermal Response For Ratiometric Optical Thermometrymentioning
confidence: 99%
“…[ 8 ] Moreover, the energy transfer process could happen between the traps and chromophores, so it is possible to achieve luminescence enhancement of the emitter by controlling the species of defects. [ 9 ] In terms of inorganic luminescence materials within the nanoscale, surface engineering techniques such as surface plasmonic resonance [ 10 ] , core–shell structure, [ 11 ] and dye‐sensitizing [ 12 ] are effective ways to enhance the brightness of nanoparticles. Despite some progress, the abovementioned luminescence modulation approaches are irreversible, severely restricting the broader application of inorganic luminescent materials.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2022, American Chemical Society. Reproduced with permission [9]. Reproduced with permission [14].…”
mentioning
confidence: 99%